Eosinophils, T-lymphocytes, mast cells, neutrophils, and macrophages in bronchial biopsy specimens from atopic subjects with asthma: Comparison with biopsy specimens from atopic subjects without asthma and normal control subjects and relationship to bronchial hyperresponsiveness - Bradley, Brian L.; Azzawi, May; Jacobson, Mikila; Assoufi, Basil; Collins, John V.; Irani, Anne-marie A.; Schwartz, Lawrence B.; Durham, Stephen R.; Jeffery, Peter K.; Kay, A.Barry (Journal of allergy and clinical immunology, 1991)
Bronchial biopsy specimens were obtained by fiberoptic bronchoscopy from 21 atopic subjects with asthma, 10 atopic subjects without asthma, and 12 normal healthy control subjects. With immunohistochemical techniques and a panel of monoclonal antibodies, inflammatory cells were identified and counted in the bronchial mucosa. The mean number of leukocytes (CD45 +) and T-lymphocytes (CD3 +, CD4 +, and CD8 +) at two airway levels in the subjects with asthma tended to be higher than in the other groups, but this difference did not achieve statistical significance. Similarly, there were no significant differences in the numbers of mucosal-type or connective tissue-type mast cells, elastase-positive neutrophils, or Leu-M3 + cells in the airway mucosa of subjects with asthma compared with atopic subjects without asthma and healthy control subjects. In contrast, significantly more interleukin-2 receptor-positive (CD25 +) cells and “activated” (EG2 +) eosinophils (EOSs) were present in the airways of subjects with asthma at both proximal and subsegmental biopsy sites. When the relationships between numbers of T-lymphocytes, activated (CD25 +) cells, and EOSs were analyzed, there were positive correlations between CD3 and EG2, between CD3 and CD25, and between CD25 and EG2 positive cells in the airways of subjects with asthma. Furthermore, the ratio of EG2 + to CD45 + cells correlated with the provocative concentration of methacholine that caused a 20% decrease of FEV 1 in hyperresponsive subjects. Although these associations do not prove a causal relationship, the results support the hypothesis that activated (CD25) T-lymphocytes release products which regulate recruitment of EOSs into the airway wall. In addition, our findings suggest that, in the large airways at least, asthma is not associated with hyperplasia of either mucosal-type or connective tissue-type mast cell.